Homeopathic Medicines and Pancreatic Pathology - Hossain, Azmal (Homœopathic Links, 2017)
In this article, homeopathic medicines are used to treat a space-occupying lesion and calcifying pancreatitis with calculus. In such deep-seated pathology, low potency medicines produce the desired result and avoid the need for surgery. Wide clinical trials show that some homeopathic medicines are very useful in the treatment of such chronic diseases.
Keywords: Insulin; Chyme; Islets of Langerhans; Pancreatitis; CA pancreas; Anti-miasmatics; Chamomilla; Calcarea arsenicosum